The SPICA-SAFARI Detector System: TES Detector Arrays With Frequency-Division Multiplexed SQUID Readout - Jackson, B. D.; de Korte, P. A. J.; van der Kuur, J.; Mauskopf, P. D.; Beyer, J.; Bruijn, M. P.; Cros, A.; Gao, J.; Griffin, D.; den Hartog, R.; Kiviranta, M.; de Lange, G.; et al. (IEEE transactions on terahertz science and technology, 2012)
The SAFARI instrument is a far-infrared imaging Fourier transform spectrometer for JAXA's SPICA mission. Taking advantage of the low emission of SPICA's 5 K telescope, SAFARI will provide sky background-limited, Nyquist-sampled spectroscopic imaging of a 2 ' × 2 ' field-of-view over 34-210 μm, creating significant new possibilities for far-infrared astronomy. SAFARI's aggressive science goals drive the development of a unique detector system combining large-format Transition Edge Sensor arrays and frequency division multiplexed SQUID readout with a high 160x multiplexing factor. The detectors and their cold readout electronics are packaged into 3 focal plane arrays that will be integrated into SAFARI's focal plane unit. Here we present the preliminary system design and current development status of the SAFARI detector system.